Une anthropologie amphibienne : La production du lieu à la confluence du territoire/de la terre et de l'eau - Gagné, Karine; Rasmussen, Mattias Borg (Anthropologica, 2017)
Amid global climate change and an uneven global political economy that preys on natural resources, landscapes are reshaped at the confluence of land and water, concretely and abstractly. Focusing on the production of place, we suggest that at their point of convergence, there is relational ontology between land and water. This constitutive relationality is the basis of what we call an amphibious anthropology. By foregrounding temporality, movement, and ways of knowing, we aim to grasp the experience of places at the confluence of land and water, and to probe into the specificities of life in such landscapes, or into various amphibious anthropologies.